Examining the student and teacher feedback on concept mapping as a teaching and learning method - El Amouri, Souher; Zerish Nkosi, Zethu (International Journal of Advanced Nursing Studies, 2024)
Background: Nursing students struggle to link theory to practice; therefore, nurse educators are requested to use innovative methods to help them in this regard such as the concept mapping. Purpose: to examine the effectiveness of concept mapping as a teaching learning method in clinical setting. Method: A mixed method approach was used to student nurse and educators. A Likert scale of 15 items with 4 open ended questions was used to assess the effectiveness of the method in improving the students’ care plan. For qualitative, teacher’ reflection was used to assess the teacher perception about the effectiveness of concept map as a teaching learning method. Results: This study indicated concept mapping is an effective method in teaching in clinical setting, developing appropriate care plan and promoting critical thinking. The result showed that there is significant difference between the mean scores of participants in relation to critical thinking and usage of concept map in clinical setting, however there was no difference in regards of usage of concept map in developing care plan. Conclusion: Nurse Educators should consider the use of concept mapping as a way of teaching and learning process in order to improve critical thinking and quality of care.